A phenomenological attempt at understanding otherness - A. KOVÁCS (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2017)
The phenomenology of otherness is not satisfied with the reductionist definitions of the classical anthropological conceptions. The latter have identified the essence of man in his rationality, morality, createdness, or the possibility of moral and aesthetic self-perfection. The monolithic definition of human essence, based on uniform criteria, seems today one-sided and outdated. The parallel effects of cultural diversification, the pluralized political and social system, and multilingualism have directly and inevitably confronted us with otherness and strangeness. We could even say that we can understand our identity primarily through the experience of otherness. We will reach our conclusions related to the phenomenological constitutive of otherness by way of the interpretation of the relevant ideas of Baudrillad, Guillaume and Lévinas.